Heat-aging-resistant holographic polymer dispersed liquid crystal material, grating device and preparation method thereof
By introducing polyurethane acrylate and monomers with different functionalities into the holographic polymer dispersed liquid crystal material, the thermal degradation problem of the material at high temperature is solved through the synergistic effect of cross-linking of polymer monomers, and the thermal stability of the device is improved and service life and reduce production costs.
Patent Information
- Application Number
- CN202411388110.X
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2024-10-08
- Publication Date
- 2025-01-03
- Estimated Expiration
- 2044-10-08
AI Technical Summary
Holographic polymer dispersed liquid crystal materials are prone to thermal degradation in high temperature environments, resulting in insufficient thermal aging resistance and affecting the stability and service life of the device.
By introducing polyurethane acrylate and monomers with different functionalities into the holographic polymer dispersed liquid crystal material, the cross-linking rigidity between polymer monomers and the heat resistance of the material is improved through the synergistic effect of cross-linking between the four types of polymer monomers. Aging performance.
It significantly improves the thermal stability of holographic polymer dispersed liquid crystal materials and the comprehensive performance and service life of grating devices, while reducing production costs and improving production convenience.
Smart Images

Figure SMS_1
Abstract
Description
Technical Field
[0001] The present invention relates to the field of holographic projection display, and more specifically, to a heat-aging-resistant holographic polymer dispersed liquid crystal material, a grating device and a preparation method thereof. Background Art
[0002] Liquid crystal is one of the fastest-growing, most widely used and most closely related optoelectronic materials since the last century. It is still widely used in the display of various electronic devices. Thanks to the tunable properties of liquid crystal materials, the arrangement direction of liquid crystal molecules can be controlled by applying external fields such as electric fields, magnetic fields, and heat, thereby realizing different functions of the device, greatly improving the multi-dimensional flexible controllability of devices in the current electronics industry. Among them, polymer dispersed liquid crystal (PDLC) is an optoelectronic functional device based on liquid crystal / polymer materials. It mainly transforms the mixture of liquid crystal and prepolymer into liquid crystal droplets dispersed in the polymer substrate by photopolymerization or thermal polymerization to cause phase separation. Then, the electrical control characteristics of liquid crystal are used to control the orientation of liquid crystal molecules by applying an external voltage, thereby changing the refractive index of liquid crystal to match or mismatch the refractive index of polymer, resulting in the polymer dispersed liquid crystal film switching between light transmission or light scattering under the action of an electric field.
[0003] Holographic Polymer Dispersed Liquid Crystal (H-PDLC) is a combination of holographic technology and polymer dispersed liquid crystal. It is a composite material with holographic display function and a certain ordered arrangement structure system. H-PDLC is formed by periodic arrangement of polymer-rich phase and liquid crystal-rich phase. It is formed by polymerization-induced phase separation under coherent laser. Specifically, a laser beam is divided into two coherent beams of equal light intensity, and then converged to obtain an interference light field with a sinusoidal distribution of light intensity, and light intensity modulation is generated in the interference area; in the interference bright fringe area (i.e., coherent bright area), the photoinitiator system absorbs light energy, generates active free radicals, and initiates monomer polymerization. The polymerization reaction causes the chemical potential of the system to change, causing the monomer to diffuse from the coherent dark area to the coherent bright area, and the liquid crystal diffuses to the coherent dark area, and finally produces a holographic grating structure composed of alternating polymer-rich phases and liquid crystal-rich phases. Holographic polymer dispersed liquid crystal materials have a variety of functions and have been widely used in electro-optical response photonic crystals, color 3D holographic image storage, distributed feedback lasers, sensors and other fields. In addition, due to its excellent electro-optical response characteristics and high refractive index modulation, holographic polymer dispersed liquid crystal materials also show great application potential in the field of augmented reality.
[0004] As a composite material, holographic polymer dispersed liquid crystal materials usually cause problems such as polymer matrix degradation under high temperature environment. The reason is that when thermally degradable polymers are exposed to high temperature for a long time, the movement of polymer chains will intensify. Once the dissociation energy of chemical bonds is exceeded, thermal degradation of polymer chains will occur. The thermal degradation of polymers can be roughly divided into three categories: depolymerization, random chain scission, and side group removal. Among them, depolymerization and random chain scission are to break polymers into monomers and low molecular weight substances, so that the degree of polymerization is reduced. Side group removal may remove side groups while keeping the degree of polymerization basically unchanged, so that the molecular weight of polymers is slightly reduced. The heat aging resistance of grating devices prepared by holographic polymer dispersed liquid crystal materials mainly depends on the polymer materials in the polymer-rich area. Under long-term high temperature conditions, the polymers in the polymer-rich area will undergo thermal degradation, and the molecular chains will break into small molecules or groups will fall off, so that the small liquid crystal molecules in the liquid crystal area will flow into the cracks of the polymer, resulting in an increase in the overall refractive index of the polymer area and shortening the refractive index difference with the liquid crystal area. Therefore, in order for the holographic polymer dispersed liquid crystal material to maintain stable performance for a long time, it is necessary to improve the thermal stability of the material. Specifically, it is mainly necessary to increase the heat aging resistance of the high molecular weight polymer in the polymer region. Summary of the invention
[0005] The present invention aims to overcome at least one defect of the above-mentioned prior art, and provides a heat-aging-resistant holographic polymer dispersed liquid crystal material, a grating device and a preparation method thereof, thereby improving the thermal stability of the holographic polymer dispersed liquid crystal material, and further improving the comprehensive performance and service life of the holographic polymer dispersed liquid crystal material and the grating device prepared therefrom.
[0006] The technical solution adopted by the present invention is firstly to provide a heat-aging-resistant holographic polymer dispersed liquid crystal material, which comprises, by mass percentage:
[0007] Photoinitiator: 0.5-2%,
[0008] Co-initiator: 0.5-10%,
[0009] LCD: 35-55%,
[0010] Polyurethane acrylate: 5-20%,
[0011] Solvent: 5-15%,
[0012] First monomer: 5-40%,
[0013] Second monomer: 5-40%,
[0014] The third monomer: 1-10%;
[0015] The polyurethane acrylate is selected from one or more of aliphatic polyurethane acrylate, aromatic polyurethane acrylate, and fluorine-modified polyurethane acrylate;
[0016] The first monomer is selected from one or more of benzyl acrylate, benzyl methacrylate, and dicyclopentenyl acrylate;
[0017] The second monomer is selected from one or more of tricyclodecane dimethanol dimethacrylate, ethoxylated bisphenol A diacrylate, and 1,2-dioxanediol diacrylate;
[0018] The third monomer is tris(2-hydroxyethyl)isocyanurate triacrylate.
[0019] In the technical solution, polyurethane acrylate and first monomers, second monomers and third monomers with different functionalities are introduced into the holographic polymer dispersed liquid crystal material, and the cross-linking rigidity between the polymer monomers in the holographic polymer dispersed liquid crystal material is improved through the cross-linking synergistic effect between the four types of polymer monomers, and the heat aging resistance of the material is improved. Specifically, by adjusting the types and proportions of the added polyurethane acrylate and the first monomer, the second monomer and the third monomer, the efficiency of the polymerization reaction between the monomers in the material can be adjusted, and the diffraction efficiency and function of the prepared holographic grating device can be adjusted and improved. Specifically, the polyurethane acrylate is selected from one or more of aliphatic polyurethane acrylate, aromatic polyurethane acrylate, and fluorine-modified polyurethane acrylate; the first monomer is a monofunctional monomer, selected from one or more of benzyl acrylate, benzyl methacrylate, and dicyclopentenyl acrylate; the second monomer is a difunctional monomer, selected from one or more of tricyclodecane dimethanol dimethacrylate, ethoxylated bisphenol A diacrylate, and dioxane diol diacrylate; the third monomer is a trifunctional monomer, specifically, tris (2-hydroxyethyl) isocyanuric acid triacrylate. In this technical solution, the thermal stability of the holographic polymer dispersed liquid crystal material is improved by the combined use of polyurethane acrylate and three types of polymer monomers, so that the holographic volume grating device prepared by the holographic polymer dispersed liquid crystal material has better comprehensive performance and service life. At the same time, the selection of polymer monomers contained in the holographic polymer dispersed liquid crystal material is diverse, and the source of its raw materials is wide and easy to obtain, which improves the production convenience and reduces the production cost while ensuring the function of the holographic volume grating device.
[0020] Furthermore, the photoinitiator is selected from one or more of rose bengal, camphorquinone, methylene blue and ethyl eosin.
[0021] Furthermore, the co-initiator is selected from one or more of N,N-dimethylaniline, Lencolo 5031 and N-phenylglycine.
[0022] Furthermore, the liquid crystal is selected from one or more of E7, E63, P0616A, BL038 and TEB30A.
[0023] Furthermore, the solvent is selected from one or more of cyclohexane, dichloromethane, dimethylformamide and N-ethylpyrrolidone.
[0024] Another object of the present invention is to provide a method for preparing a holographic polymer dispersed liquid crystal grating device. The preparation method has a simple process, does not require post-curing, has low production cost, and high production efficiency. The preparation method specifically comprises the following steps:
[0025] The heat-aging-resistant holographic polymer dispersed liquid crystal material provided in the technical solution is mixed and poured into a liquid crystal box, placed still in a dark room, and then interference exposed under the interference light field of a double-beam light source.
[0026] Optionally, the interference exposure time is 1-5 min, and the irradiation power is 4-6 mW / cm 2 ; The angle between the dual-beam light sources is 30°-60°.
[0027] Preferably, a double beam angle of 45° and an optical power of 5 mW / cm 2 The material was exposed to a dual-beam light source for 3 min to prepare a holographic polymer dispersed liquid crystal grating device.
[0028] Optionally, the thickness of the liquid crystal box is 5 μm-10 μm.
[0029] Optionally, the mixing step is: firstly oscillating and mixing the heat-aging-resistant holographic polymer dispersed liquid crystal material with a vortex oscillator for 0.5-3 minutes, and then placing it in an ultrasonic instrument for ultrasonic mixing at 60° C. for 20-40 minutes to obtain a holographic polymer dispersed liquid crystal mixed liquid;
[0030] The holographic polymer dispersed liquid crystal mixed liquid is filled into a liquid crystal box under vacuum atmosphere and placed in a 60° C. oven for 15-25 minutes.
[0031] Preferably, the heat-aging-resistant holographic polymer dispersed liquid crystal materials are mixed uniformly to obtain a heat-aging-resistant holographic polymer dispersed liquid crystal mixed liquid.
[0032] The heat-aging-resistant holographic polymer dispersed liquid crystal mixed liquid is filled into a liquid crystal box with a thickness of 5 μm under vacuum conditions and allowed to stand in a dark room for 1 hour.
[0033] Another object of the present invention is to provide a holographic polymer dispersed liquid crystal grating device, which is prepared by the preparation method provided by the technical solution.
[0034] Compared with the prior art, the beneficial effects of the present invention are as follows: by introducing polyurethane acrylate and the first monomer, the second monomer and the third monomer with different functionalities to prepare a holographic polymer dispersed liquid crystal material, by adjusting the types and proportions of the added polyurethane acrylate and the first monomer, the second monomer and the third monomer, the efficiency of the polymerization reaction between the monomers in the material can be adjusted, and the diffraction efficiency and function of the prepared holographic volume grating device can be adjusted and improved. The cross-linking synergistic effect between the four types of polymer monomers improves the cross-linking rigidity between the polymer monomers in the holographic polymer dispersed liquid crystal material, and at the same time improves the heat aging resistance of the material, and improves the thermal stability of the holographic polymer dispersed liquid crystal material, so that the holographic volume grating device prepared by the holographic polymer dispersed liquid crystal material has better comprehensive performance and service life. At the same time, the polymer monomers contained in the holographic polymer dispersed liquid crystal material are diverse in selection, and the source of the raw materials is wide and easy to obtain, which improves the production convenience and reduces the production cost while ensuring the function of the holographic volume grating device. DETAILED DESCRIPTION
[0035] It should be noted that the following detailed descriptions are illustrative and are intended to provide further explanation of the present application. Unless otherwise specified, all technical and scientific terms used herein have the same meanings as those commonly understood by those skilled in the art to which the present application belongs.
[0036] It should be noted that the terms used herein are only for describing specific embodiments and are not intended to limit the exemplary embodiments according to the present application. As used herein, unless the context clearly indicates otherwise, the singular form is also intended to include the plural form. In addition, it should be understood that when the terms "comprise" and / or "include" are used in this specification, it indicates the presence of features, steps, operations, devices, components and / or combinations thereof.
[0037] The present invention is now further described in conjunction with specific examples. The following examples are only for explaining the present invention, but do not constitute a limitation of the present invention. The test samples and test processes used in the following examples include the following (if the specific experimental conditions are not specified in the examples, they are usually carried out according to conventional conditions or according to the conditions recommended by the reagent company; the reagents, consumables, etc. used in the following examples, unless otherwise specified, can all be obtained from commercial channels).
[0038] Example 1
[0039] This embodiment provides a heat-aging resistant holographic polymer dispersed liquid crystal material, a holographic polymer dispersed liquid crystal grating device and a preparation method thereof, specifically comprising the following steps:
[0040] (1) Weigh the raw materials from the brown sample bottle according to the following mass percentages:
[0041] Methylene blue 1.5%, N-phenylglycine 5%, TEB30A 35%, benzyl acrylate 16%, aliphatic polyurethane acrylate 12%, tricyclodecane dimethanol dimethacrylate 17%, tris(2-hydroxyethyl)isocyanuric acid triacrylate 6%, dimethylformamide 3%, N-ethylpyrrolidone 4.5%.
[0042] (2) Preparation of holographic polymer dispersed liquid crystal materials:
[0043] The weighed raw materials are mixed evenly to obtain a heat-resistant and aging-resistant holographic polymer dispersed liquid crystal mixed liquid.
[0044] (3) Preparation of holographic polymer dispersed liquid crystal grating devices:
[0045] The heat-aging-resistant holographic polymer dispersed liquid crystal mixed liquid is filled into a liquid crystal box with a thickness of 5 μm under vacuum conditions and allowed to stand in a dark room for 1 hour.
[0046] Then, a double beam with an angle of 45° and an optical power of 5 mW / cm 2 The material was exposed with a dual-beam light source for 3 minutes to obtain a holographic polymer dispersed liquid crystal grating device.
[0047] (4) Diffraction efficiency test and haze test:
[0048] The specific steps of the diffraction efficiency test are as follows: testing the diffraction efficiency of the holographic polymer dispersed liquid crystal grating device by using a grating diffraction efficiency tester.
[0049] The specific steps of the haze test are: using a haze meter according to GB 2410-2008 "Test method for light transmittance and haze of transparent plastics" to test the haze of the above holographic polymer dispersed liquid crystal grating device at 23±2°C.
[0050] (5) Aging test:
[0051] The specific steps of the aging test are: using a heat aging test box according to GB / T7141-2008 "Plastics Thermal Aging Test Method", the above holographic polymer dispersed liquid crystal grating device is aged in 80° C. hot air for 200 hours.
[0052] The holographic polymer dispersed liquid crystal grating device after the aging test is subjected to a diffraction efficiency test and a haze test again under the same test conditions, and the diffraction efficiency change rate and the haze change rate of the holographic polymer dispersed liquid crystal grating device after the aging test are obtained.
[0053] Example 2
[0054] This embodiment provides a heat-aging resistant holographic polymer dispersed liquid crystal material, a holographic polymer dispersed liquid crystal grating device and a preparation method thereof, specifically comprising the following steps:
[0055] (1) Weigh the raw materials from the brown sample bottle according to the following mass percentages:
[0056] Rose Red 1%, Lencolo 5031 2.5%, E7 38%, aromatic polyurethane acrylate 15%, benzyl acrylate 14%, 1,2-dioxanediol diacrylate 15%, tris(2-hydroxyethyl)isocyanurate triacrylate 8%, dimethylformamide 6.5%.
[0057] (2) Preparation of holographic polymer dispersed liquid crystal materials:
[0058] The weighed raw materials are mixed evenly to obtain a heat-resistant and aging-resistant holographic polymer dispersed liquid crystal mixed liquid.
[0059] (3) Preparation of holographic polymer dispersed liquid crystal grating devices:
[0060] The heat-aging-resistant holographic polymer dispersed liquid crystal mixed liquid is filled into a liquid crystal box with a thickness of 5 μm under vacuum conditions and allowed to stand in a dark room for 1 hour.
[0061] Then, a double beam with an angle of 45° and an optical power of 5 mW / cm 2 The material was exposed with a dual-beam light source for 3 minutes to obtain a holographic polymer dispersed liquid crystal grating device.
[0062] (4) Diffraction efficiency test and haze test:
[0063] The specific steps of the diffraction efficiency test are as follows: testing the diffraction efficiency of the holographic polymer dispersed liquid crystal grating device by using a grating diffraction efficiency tester.
[0064] The specific steps of the haze test are: using a haze meter according to GB 2410-2008 "Test method for light transmittance and haze of transparent plastics" to test the haze of the above holographic polymer dispersed liquid crystal grating device at 23±2°C.
[0065] (5) Aging test:
[0066] The specific steps of the aging test are: using a heat aging test box according to GB / T7141-2008 "Plastics Thermal Aging Test Method", the above holographic polymer dispersed liquid crystal grating device is aged in 80° C. hot air for 200 hours.
[0067] The holographic polymer dispersed liquid crystal grating device after the aging test is subjected to a diffraction efficiency test and a haze test again under the same test conditions, and the diffraction efficiency change rate and the haze change rate of the holographic polymer dispersed liquid crystal grating device after the aging test are obtained.
[0068] Example 3
[0069] This embodiment provides a heat-aging resistant holographic polymer dispersed liquid crystal material, a holographic polymer dispersed liquid crystal grating device and a preparation method thereof, specifically comprising the following steps:
[0070] (1) Weigh the raw materials from the brown sample bottle according to the following mass percentages:
[0071] Ethyl eosin 2%, N, N-dimethylaniline 3%, E63 30%, dicyclopentenyl acrylate 18%, fluorine-modified polyurethane acrylate 10%, 17% dioxane diol diacrylate, 10% tris(2-hydroxyethyl)isocyanuric acid triacrylate, 5% cyclohexane, 5% N-ethylpyrrolidone.
[0072] (2) Preparation of holographic polymer dispersed liquid crystal materials:
[0073] The weighed raw materials are mixed evenly to obtain a heat-resistant and aging-resistant holographic polymer dispersed liquid crystal mixed liquid.
[0074] (3) Preparation of holographic polymer dispersed liquid crystal grating devices:
[0075] The heat-aging-resistant holographic polymer dispersed liquid crystal mixed liquid is filled into a liquid crystal box with a thickness of 5 μm under vacuum conditions and allowed to stand in a dark room for 1 hour.
[0076] Then, a double beam with an angle of 45° and an optical power of 5 mW / cm 2 The material was exposed with a dual-beam light source for 3 minutes to obtain a holographic polymer dispersed liquid crystal grating device.
[0077] (4) Diffraction efficiency test and haze test:
[0078] The specific steps of the diffraction efficiency test are as follows: testing the diffraction efficiency of the holographic polymer dispersed liquid crystal grating device by using a grating diffraction efficiency tester.
[0079] The specific steps of the haze test are: using a haze meter according to GB 2410-2008 "Test method for light transmittance and haze of transparent plastics" to test the haze of the above holographic polymer dispersed liquid crystal grating device at 23±2°C.
[0080] (5) Aging test:
[0081] The specific steps of the aging test are: using a heat aging test box according to GB / T7141-2008 "Plastics Thermal Aging Test Method", the above holographic polymer dispersed liquid crystal grating device is aged in 80° C. hot air for 200 hours.
[0082] The holographic polymer dispersed liquid crystal grating device after the aging test is subjected to a diffraction efficiency test and a haze test again under the same test conditions, and the diffraction efficiency change rate and the haze change rate of the holographic polymer dispersed liquid crystal grating device after the aging test are obtained.
[0083] Example 4
[0084] This embodiment provides a heat-aging resistant holographic polymer dispersed liquid crystal material, a holographic polymer dispersed liquid crystal grating device and a preparation method thereof, specifically comprising the following steps:
[0085] (1) Weigh the raw materials from the brown sample bottle according to the following mass percentages:
[0086] Camphorquinone 1%, Lencolo 5031 3%, P0616A 32%, aromatic polyurethane acrylate 16%, benzyl methacrylate 14%, ethoxylated bisphenol A diacrylate 15%, tris(2-hydroxyethyl) isocyanurate triacrylate 13%, dichloromethane 6%.
[0087] (2) Preparation of holographic polymer dispersed liquid crystal materials:
[0088] The weighed raw materials are mixed evenly to obtain a heat-resistant and aging-resistant holographic polymer dispersed liquid crystal mixed liquid.
[0089] (3) Preparation of holographic polymer dispersed liquid crystal grating devices:
[0090] The heat-aging-resistant holographic polymer dispersed liquid crystal mixed liquid is filled into a liquid crystal box with a thickness of 5 μm under vacuum conditions and allowed to stand in a dark room for 1 hour.
[0091] Then, a double beam with an angle of 45° and an optical power of 5 mW / cm 2 The material was exposed with a dual-beam light source for 3 minutes to obtain a holographic polymer dispersed liquid crystal grating device.
[0092] (4) Diffraction efficiency test and haze test:
[0093] The specific steps of the diffraction efficiency test are as follows: testing the diffraction efficiency of the holographic polymer dispersed liquid crystal grating device by using a grating diffraction efficiency tester.
[0094] The specific steps of the haze test are: using a haze meter according to GB 2410-2008 "Test method for light transmittance and haze of transparent plastics" to test the haze of the above holographic polymer dispersed liquid crystal grating device at 23±2°C.
[0095] (5) Aging test:
[0096] The specific steps of the aging test are: using a heat aging test box according to GB / T7141-2008 "Plastics Thermal Aging Test Method", the above holographic polymer dispersed liquid crystal grating device is aged in 80° C. hot air for 200 hours.
[0097] The holographic polymer dispersed liquid crystal grating device after the aging test is subjected to a diffraction efficiency test and a haze test again under the same test conditions, and the diffraction efficiency change rate and the haze change rate of the holographic polymer dispersed liquid crystal grating device after the aging test are obtained.
[0098] Example 5
[0099] This embodiment provides a heat-aging resistant holographic polymer dispersed liquid crystal material, a holographic polymer dispersed liquid crystal grating device and a preparation method thereof, specifically comprising the following steps:
[0100] (1) Weigh the raw materials from the brown sample bottle according to the following mass percentages:
[0101] Camphorquinone 1%, N-phenylglycine 3%, BL038 35%, aliphatic polyurethane acrylate 14%, dicyclopentenyl acrylate 14%, tricyclodecane dimethanol dimethacrylate 13%, tris(2-hydroxyethyl)isocyanuric acid triacrylate 14%, dichloromethane 3%, dimethylformamide 3%.
[0102] (2) Preparation of holographic polymer dispersed liquid crystal materials:
[0103] The weighed raw materials are mixed evenly to obtain a heat-resistant and aging-resistant holographic polymer dispersed liquid crystal mixed liquid.
[0104] (3) Preparation of holographic polymer dispersed liquid crystal grating devices:
[0105] The heat-aging-resistant holographic polymer dispersed liquid crystal mixed liquid is filled into a liquid crystal box with a thickness of 5 μm under vacuum conditions and allowed to stand in a dark room for 1 hour.
[0106] Then, a double beam with an angle of 45° and an optical power of 5 mW / cm 2 The material was exposed with a dual-beam light source for 3 minutes to obtain a holographic polymer dispersed liquid crystal grating device.
[0107] (4) Diffraction efficiency test and haze test:
[0108] The specific steps of the diffraction efficiency test are as follows: testing the diffraction efficiency of the holographic polymer dispersed liquid crystal grating device by using a grating diffraction efficiency tester.
[0109] The specific steps of the haze test are: using a haze meter according to GB 2410-2008 "Test method for light transmittance and haze of transparent plastics" to test the haze of the above holographic polymer dispersed liquid crystal grating device at 23±2°C.
[0110] (5) Aging test:
[0111] The specific steps of the aging test are: using a heat aging test box according to GB / T7141-2008 "Plastics Thermal Aging Test Method", the above holographic polymer dispersed liquid crystal grating device is aged in 80° C. hot air for 200 hours.
[0112] The holographic polymer dispersed liquid crystal grating device after the aging test is subjected to a diffraction efficiency test and a haze test again under the same test conditions, and the diffraction efficiency change rate and the haze change rate of the holographic polymer dispersed liquid crystal grating device after the aging test are obtained.
[0113] Comparative Example 1
[0114] This comparative example provides a heat-aging resistant holographic polymer dispersed liquid crystal material, a holographic polymer dispersed liquid crystal grating device and a preparation method thereof, specifically comprising the following steps:
[0115] (1) Weigh the raw materials from the brown sample bottle according to the following mass percentages:
[0116] Ethyl eosin 1%, N-phenylglycine 5%, BL038 38%, benzyl acrylate 20%, 18% 1,2-dioxanediol diacrylate, 8% tris(2-hydroxyethyl)isocyanuric acid triacrylate, and 10% dimethylformamide.
[0117] (2) Preparation of holographic polymer dispersed liquid crystal materials:
[0118] The weighed raw materials are mixed evenly to obtain a heat-resistant and aging-resistant holographic polymer dispersed liquid crystal mixed liquid.
[0119] (3) Preparation of holographic polymer dispersed liquid crystal grating devices:
[0120] The heat-aging-resistant holographic polymer dispersed liquid crystal mixed liquid is filled into a liquid crystal box with a thickness of 5 μm under vacuum conditions and allowed to stand in a dark room for 1 hour.
[0121] Then, a double beam with an angle of 45° and an optical power of 5 mW / cm 2 The material was exposed with a dual-beam light source for 3 minutes to obtain a holographic polymer dispersed liquid crystal grating device.
[0122] (4) Diffraction efficiency test and haze test:
[0123] The specific steps of the diffraction efficiency test are as follows: testing the diffraction efficiency of the holographic polymer dispersed liquid crystal grating device by using a grating diffraction efficiency tester.
[0124] The specific steps of the haze test are: using a haze meter according to GB 2410-2008 "Test method for light transmittance and haze of transparent plastics" to test the haze of the above holographic polymer dispersed liquid crystal grating device at 23±2°C.
[0125] (5) Aging test:
[0126] The specific steps of the aging test are: using a heat aging test box according to GB / T7141-2008 "Plastics Thermal Aging Test Method", the above holographic polymer dispersed liquid crystal grating device is aged in 80° C. hot air for 200 hours.
[0127] The holographic polymer dispersed liquid crystal grating device after the aging test is subjected to a diffraction efficiency test and a haze test again under the same test conditions, and the diffraction efficiency change rate and the haze change rate of the holographic polymer dispersed liquid crystal grating device after the aging test are obtained.
[0128] Comparative Example 2
[0129] This comparative example provides a heat-aging resistant holographic polymer dispersed liquid crystal material, a holographic polymer dispersed liquid crystal grating device and a preparation method thereof, specifically comprising the following steps:
[0130] (1) Weigh the raw materials from the brown sample bottle according to the following mass percentages:
[0131] Rose Red 1%, N, N-dimethylaniline 5%, E7 38%, aliphatic polyurethane acrylate 7%, ethyl acrylate 18%, 1,4-butanediol dimethacrylate 15%, pentaerythritol triacrylate 10%, dimethylformamide 3%, N-ethylpyrrolidone 3%.
[0132] (2) Preparation of holographic polymer dispersed liquid crystal materials:
[0133] The weighed raw materials are mixed evenly to obtain a heat-resistant and aging-resistant holographic polymer dispersed liquid crystal mixed liquid.
[0134] (3) Preparation of holographic polymer dispersed liquid crystal grating devices:
[0135] The heat-aging-resistant holographic polymer dispersed liquid crystal mixed liquid is filled into a liquid crystal box with a thickness of 5 μm under vacuum conditions and allowed to stand in a dark room for 1 hour.
[0136] Then, a double beam with an angle of 45° and an optical power of 5 mW / cm 2 The material was exposed with a dual-beam light source for 3 minutes to obtain a holographic polymer dispersed liquid crystal grating device.
[0137] (4) Diffraction efficiency test and haze test:
[0138] The specific steps of the diffraction efficiency test are as follows: testing the diffraction efficiency of the holographic polymer dispersed liquid crystal grating device by using a grating diffraction efficiency tester.
[0139] The specific steps of the haze test are: using a haze meter according to GB 2410-2008 "Test method for light transmittance and haze of transparent plastics" to test the haze of the above holographic polymer dispersed liquid crystal grating device at 23±2°C.
[0140] (5) Aging test:
[0141] The specific steps of the aging test are: using a heat aging test box according to GB / T7141-2008 "Plastic Thermal Aging Test Method", the above-mentioned holographic polymer dispersed liquid crystal grating device is aged in 80° C. hot air for 200 hours.
[0142] The holographic polymer dispersed liquid crystal grating device after the aging test is subjected to a diffraction efficiency test and a haze test again under the same test conditions, and the diffraction efficiency change rate and the haze change rate of the holographic polymer dispersed liquid crystal grating device after the aging test are obtained.
[0143] Comparative Example 3
[0144] This comparative example provides a heat-aging resistant holographic polymer dispersed liquid crystal material, a holographic polymer dispersed liquid crystal grating device and a preparation method thereof, specifically comprising the following steps:
[0145] (1) Weigh the raw materials from the brown sample bottle according to the following mass percentages:
[0146] Ethyl eosin 2%, N,N-dimethylaniline 3%, E63 30%, dicyclopentenyl acrylate 18%, benzyl acrylate 10%, 17% 1,2-dioxanediol diacrylate, 10% tris(2-hydroxyethyl)isocyanuric acid triacrylate, 5% cyclohexane, 5% N-ethylpyrrolidone.
[0147] (2) Preparation of holographic polymer dispersed liquid crystal materials:
[0148] The weighed raw materials are mixed evenly to obtain a heat-resistant and aging-resistant holographic polymer dispersed liquid crystal mixed liquid.
[0149] (3) Preparation of holographic polymer dispersed liquid crystal grating devices:
[0150] The heat-aging-resistant holographic polymer dispersed liquid crystal mixed liquid is filled into a liquid crystal box with a thickness of 5 μm under vacuum conditions and allowed to stand in a dark room for 1 hour.
[0151] Then, a double beam with an angle of 45° and an optical power of 5 mW / cm 2 The material was exposed with a dual-beam light source for 3 minutes to obtain a holographic polymer dispersed liquid crystal grating device.
[0152] (4) Diffraction efficiency test and haze test:
[0153] The specific steps of the diffraction efficiency test are as follows: testing the diffraction efficiency of the holographic polymer dispersed liquid crystal grating device by using a grating diffraction efficiency tester.
[0154] The specific steps of the haze test are: using a haze meter according to GB 2410-2008 "Test method for light transmittance and haze of transparent plastics" to test the haze of the above holographic polymer dispersed liquid crystal grating device at 23±2°C.
[0155] (5) Aging test:
[0156] The specific steps of the aging test are: using a heat aging test box according to GB / T7141-2008 "Plastics Thermal Aging Test Method", the above holographic polymer dispersed liquid crystal grating device is aged in 80° C. hot air for 200 hours.
[0157] The holographic polymer dispersed liquid crystal grating device after the aging test is subjected to a diffraction efficiency test and a haze test again under the same test conditions, and the diffraction efficiency change rate and the haze change rate of the holographic polymer dispersed liquid crystal grating device after the aging test are obtained.
[0158] In Examples 1 to 5, the holographic polymer dispersed liquid crystal material is selected and combined from the polyurethane acrylate, the first monomer, the second monomer and the third monomer provided in the technical solution, wherein the polyurethane acrylate is selected from one or more of aliphatic polyurethane acrylate, aromatic polyurethane acrylate and fluorine-modified polyurethane acrylate; the first monomer is a monofunctional monomer selected from one or more of benzyl acrylate, benzyl methacrylate and dicyclopentenyl acrylate; the second monomer is a difunctional monomer selected from one or more of tricyclodecane dimethanol dimethacrylate, ethoxylated bisphenol A diacrylate and dioxane hexaglycol diacrylate; the third monomer is a trifunctional monomer, specifically, tris(2-hydroxyethyl)isocyanuric acid triacrylate. In Comparative Example 1, the first monomer, the second monomer and the third monomer selected in the holographic polymer dispersed liquid crystal material formed therein are all selected from the selection range of the first monomer, the second monomer and the third monomer provided in the technical solution, but the polyurethane acrylate provided in the technical solution is not added; in the holographic polymer dispersed liquid crystal material formed in Comparative Example 2, the polyurethane acrylate provided in the technical solution is added, but at least one of the first monomer, the second monomer and the third monomer selected therein is not selected from the selection range of the first monomer, the second monomer and the third monomer provided in the technical solution;
[0159] The diffraction efficiency change rate results of the 8 holographic polymer dispersed liquid crystal materials and grating devices prepared therefrom in Examples 1 to 5 and Comparative Examples 1 to 3 after aging tests are shown in the following table:
[0160]
[0161] By comparing the embodiments and the comparative examples, it can be found that the obtained diffraction efficiency change rate results after the aging test show that when the polyurethane acrylate, the first monomer, the second monomer and the third monomer contained in the holographic polymer dispersed liquid crystal material are selected and combined accordingly according to the polymer monomer range provided in the present invention, the absolute values of the diffraction efficiency change rate and the haze change rate of the prepared holographic polymer dispersed liquid crystal grating device after long-term aging test are greatly reduced, indicating that the holographic polymer dispersed liquid crystal material obtained in the embodiment and the grating device prepared therefrom have a smaller change in device performance under long-term thermal aging conditions, that is, they have better thermal stability and their comprehensive performance is more stable, so that the prepared holographic polymer dispersed liquid crystal grating device has better comprehensive performance and longer service life, and is also suitable for a wider range of usage scenarios.
[0162] Obviously, the above embodiments of the present invention are merely examples for clearly illustrating the technical solution of the present invention, and are not intended to limit the specific implementation methods of the present invention. Any modifications, equivalent substitutions and improvements made within the spirit and principles of the claims of the present invention shall be included in the protection scope of the claims of the present invention.
Claims
1. A heat-aging resistant holographic polymer dispersed liquid crystal material, characterized in that: In terms of mass percentage, it includes: Photoinitiator: 0.5-2%, Co-initiator: 0.5-10%, LCD: 35-55%, Polyurethane acrylate: 5-20%, Solvent: 5-15%, First monomer: 5-40%, Second monomer: 5-40%, The third monomer: 1-10%; The polyurethane acrylate is selected from one or more of aliphatic polyurethane acrylate, aromatic polyurethane acrylate, and fluorine-modified polyurethane acrylate; The first monomer is selected from one or more of benzyl acrylate, benzyl methacrylate, and dicyclopentenyl acrylate; The second monomer is selected from one or more of tricyclodecane dimethanol dimethacrylate, ethoxylated bisphenol A diacrylate, and 1,2-dioxanediol diacrylate; The third monomer is tris(2-hydroxyethyl)isocyanurate triacrylate.
2. The heat-aging resistant holographic polymer dispersed liquid crystal material according to claim 1, characterized in that: The photoinitiator is selected from one or more of rose bengal, camphorquinone, methylene blue and ethyl eosin.
3. The heat-aging resistant holographic polymer dispersed liquid crystal material according to claim 1, characterized in that: The co-initiator is selected from one or more of N,N dimethylaniline, Lencolo 5031 and N-phenylglycine.
4. The heat-aging resistant holographic polymer dispersed liquid crystal material according to claim 1, characterized in that: The liquid crystal is selected from one or more of E7, E63, P0616A, BL038 and TEB30A.
5. The heat-aging resistant holographic polymer dispersed liquid crystal material according to claim 1, characterized in that: The solvent is selected from one or more of cyclohexane, dichloromethane, dimethylformamide and N-ethylpyrrolidone.
6. A method for preparing a holographic polymer dispersed liquid crystal grating device, characterized in that: The following steps are involved: The heat-aging-resistant holographic polymer dispersed liquid crystal material according to any one of claims 1 to 5 is mixed and poured into a liquid crystal box, placed still in a dark room, and then subjected to interference exposure under the interference light field of a double-beam light source.
7. The preparation method according to claim 6, characterized in that: The interference exposure time is 1-5 minutes, and the irradiation power is 4-6 mW / cm 2 ; and the angle between the dual-beam light sources is 30°-60°.
8. The preparation method according to claim 6, characterized in that: The thickness of the liquid crystal cell is 5-10 μm.
9. The preparation method according to claim 6, characterized in that: The holographic polymer dispersed liquid crystal mixed liquid is filled into a liquid crystal box under vacuum atmosphere and left to stand in a dark room for 1 hour.
10. A holographic polymer dispersed liquid crystal grating device, characterized in that: Prepared by the preparation method according to any one of claims 6 to 9.
Citation Information
Patent Citations
Polymer dispersed liquid crystal material and method for preparing liquid crystal films from same
CN101717647A
Holographic material systems and waveguides incorporating low functionality monomers
CN111902768A